Brown Tumor as a Result of Hyperparathyroidism in an End-Stage Renal Disease Patient - Jesse M. Jakubowski; Ines Velez; Shawn A. McClure (Case Reports in Radiology)
A 49-year-old male with known history of end-stage renal disease (ESRD) presents with an intraoral exophytic mass of the right mandible. This lesion was given a histologic diagnosis of a Brown tumor. Purpose. To allow physicians to include this lesion in a differential diagnosis when evaluating patients with primary, secondary, or tertiary hyperparathyroidism.